Transforming Sustainability and Health System in Dairy Cooperatives: An Innovative Business Model Canvas For Value Creation in Western Java, Indonesia - Fadillah, Achmad; Indrawan, Dikky (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The dairy industry is in need of a paradigm shift from traditional practices to a contemporary, enhanced system. This study aims to analyze and characterize business models that bring added value to the conventional dairy business, fostering a more sustainable approach to cattle healthcare. While the amalgamation of sustainable practices and cattle health within dairy business models remains relatively unexplored, this study bridges the gap. In the month of April 2022, a cross-sectional study was carried out in selected dairy cooperative (KPS Cianjur Utara), West Java, Indonesia. By conducting a comprehensive analysis of business model frameworks pertinent to the management and staff of dairy cooperatives, a practical approach has been developed. This approach serves the purpose of assisting cooperatives in meticulously evaluating their existing models while also facilitating the creation of novel and innovative business approaches. This tool involves augmenting the Business Model Canvas (BMC), introducing novel dimensions that operationalize dairy farm and cooperative dynamics. The proposed dairy cooperative BMC framework presents a pragmatic structure for formulating and disseminating a holistic, improved model. Diverse dairy cooperative business models have been identified and extensively deliberated upon. Despite varying organizational architectures and approaches to value creation, a common thread of collaboration and adaptability to external fluctuations runs through all these models. This study lays the foundation for transformative change within the dairy sector, aligning it with contemporary sustainability objectives. Keywords: sustainable business, business model canvas, animal health, dairy business, KPS Cianjur Utara